An evaluative study of information audit and knowledge management audit (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
While defining the information audit is a tool that can be used to not only identifying strategically significant information resources, but also to identify those tasks and activities that create knowledge and those that rely on the transfer of knowledge from the other area of the organization. This article firstly describes the relationship between the information audit process and knowledge management. Secondly, introduces the seven stage information audit models. It discusses each stage of the model in terms of its contribution to the process and the desired outcomes. Concludes by examining the potential benefits of using the information audit as a foundation that can be built on as the knowledge management strategy is developed.Keywords: Information Audit. Information Management. Knowledge Management.Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/viewFile/697/1475